Analisis Peranan Pemilih Pemula dan Pentingnya Teknologi Digital Untuk Pemilihan Umum 2024 di Indonesia (Studi Kasus: Pemilih Pemula SMA Negeri 20 Makassar) - Tamrin, Usman; RS, Asmaul Husna; Arsyad, Andi Asyhary J.; Umar, Najirah; Kurniawan, Dody (Puslitbang Akademi Relawan TIK Indonesia, 2024)
This research aims to analyze the role of first-time voters, particularly high school students at SMA Negeri 20 Makassar, in facing the 2024 General Election through the utilization of digital media. The research method employed is descriptive quantitative method with the study population encompassing all students of SMA Negeri 20 Makassar, with a sample size of 208 individuals selected using random sampling method. The results of the study indicate that first-time voters can easily access political information in the current digital era through various online platforms such as social media, news websites, and political information portals. In this study, digital literacy emerges as significantly crucial in assisting students to comprehend the necessary technology and skills required to manage online information, with a success rate of digital literacy reaching 61%. The political perceptions of first-time voters are greatly influenced by social media, which serves as the primary platform. Good digital literacy enables them to access information quickly and evaluate the balance and authenticity of the information presented. Therefore, digital literacy aids students in forming critical attitudes toward political content disseminated on social media. Additionally, they also learn about the role of technology in shaping mature political views for the 2024 General Election.